2021
DOI: 10.1111/cob.12439
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide‐1 receptor agonists in the era of COVID‐19: Friend or foe?

Abstract: Summary The aim of the present manuscript is to discuss on potential pros and cons of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) as glucose‐lowering agents during COVID‐19 pandemic, and what is more to evaluate them as potential candidates for the treatment of patients, affected by COVID‐19 infection, with or even without diabetes mellitus type 2. Besides being important glucose‐lowering agents, GLP‐1RAs pose promising anti‐inflammatory and anti‐obesogenic properties, pulmonary protective effects, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…[15] In addition to stimulating postprandial insulin secretion, GLP1-RA also seems to have beneficial properties such antiinflammatory, anti-obesogenic, pulmonary protective effects and gut microbiome modulating effects. [16] Furthermore, an experimental study on rats showed that the use of GLP1-RA (liraglutide) was capable to stimulate pulmonary ACE2 expression, an enzyme that has been demonstrated to oppose the pathway that is responsible for the progression of acute respiratory distress syndrome (ARDS), including the one caused by SARS-CoV-2 infection. [17,18] However, the evidences regarding benefit of GLP-1RA in Covid-19 patients are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[15] In addition to stimulating postprandial insulin secretion, GLP1-RA also seems to have beneficial properties such antiinflammatory, anti-obesogenic, pulmonary protective effects and gut microbiome modulating effects. [16] Furthermore, an experimental study on rats showed that the use of GLP1-RA (liraglutide) was capable to stimulate pulmonary ACE2 expression, an enzyme that has been demonstrated to oppose the pathway that is responsible for the progression of acute respiratory distress syndrome (ARDS), including the one caused by SARS-CoV-2 infection. [17,18] However, the evidences regarding benefit of GLP-1RA in Covid-19 patients are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study speculated that GLP-1R agonists did not contribute to the recovery of patients with COVID-19 [ 46 ]. On the other hand, GLP-1R agonist-associated ACE2 respiratory upregulation is infrequent and shown in few animal studies only [ 47 ]. GLP-1R agonists have powerful glucose-lowering and weight loss effects [ 2 , 47 ].…”
Section: Drugs Interact With Ace2 and Nhementioning
confidence: 99%
“…On the other hand, GLP-1R agonist-associated ACE2 respiratory upregulation is infrequent and shown in few animal studies only [ 47 ]. GLP-1R agonists have powerful glucose-lowering and weight loss effects [ 2 , 47 ]. Besides, they may have anti-inflammatory and pulmonary protective effects and a beneficial impact on gut microbiome composition.…”
Section: Drugs Interact With Ace2 and Nhementioning
confidence: 99%
See 1 more Smart Citation
“…These drugs have been initially used in diabetes treatment but now are also used in the management of obesity itself. GLP-1RAs exhibit anti-inflammatory properties, exert pulmonary protective effects, and have a beneficial influence on, gut microbiome [ 23 ]. However, in some animal studies, GLP-1RAs increased ACE-2 levels promoting SARS-CoV-2 infection [ 24 ].…”
Section: Main Textmentioning
confidence: 99%